2018
DOI: 10.1007/s12274-018-2175-9
|View full text |Cite
|
Sign up to set email alerts
|

pH-sensitive and biodegradable charge-transfer nanocomplex for second near-infrared photoacoustic tumor imaging

Abstract: pH-sensitive and biodegradable charge-transfer nanocomplex for second near-infrared photoacoustic tumor imaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 52 publications
2
81
0
Order By: Relevance
“…The oxidation product of TMB could form charge transfer complex with TMB and display a characteristic absorbance at 652 nm ( Fig. 1f) 34 . The oxidaselike activity of PtCo@G was further characterized with several different oxidase substrates, such as 2, 2′azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) and o-phenylenediamine (OPD).…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation product of TMB could form charge transfer complex with TMB and display a characteristic absorbance at 652 nm ( Fig. 1f) 34 . The oxidaselike activity of PtCo@G was further characterized with several different oxidase substrates, such as 2, 2′azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) and o-phenylenediamine (OPD).…”
Section: Resultsmentioning
confidence: 99%
“…These fluorescent biodegradation products were tracked, revealing that SPN4‐6 were excreted out of mice through urine and feces within 15 days after systematic administration (Figure e,f). In another study, Xing and co‐workers reported a charge‐transfer nanocomplex (CTN) with a pH related PA signal and used it for NIR‐II PA imaging . As the increment of pH, diimine was produced as the product, leading to the disassembly of complex and the decrease of PA signals.…”
Section: Nir‐ii Pa Imagingmentioning
confidence: 99%
“…Compared to the images of the tumor without TSPNs, the signal was enhanced ∼7.0-fold at 1100 nm and ∼13.3-fold at 1300 nm. Reports on NIR-II tumor imaging 116,154 promised that it can provide high sensitivity and depth for tumor imaging compared to NIR-I window.…”
Section: Skin and Tumor Imagingmentioning
confidence: 99%
“…[110][111][112][113][114][115] The PA signal generated by NIR-II wavelengths is weak and hence effective contrast agents are often necessary for enhancing the image contrast. With the increasing demonstrations on the advantages of PAI, efforts are made to develop strong NIR-II absorbing organic, 37,[116][117][118] inorganic, [119][120][121][122][123][124][125][126] etc. Although, these nanoparticles show broad absorption spectrum in the NIR-II window, most of them are demonstrated for PAI at 1064-nm wavelength because 1064-nm nanosecond laser (Nd:YAG laser) is commercially available.…”
Section: Introductionmentioning
confidence: 99%